Baskara Putra's Self-Image as a Musician: Professionalism, Immersion, and Emotional Closeness in @wordfang's Instagram Posts - Ade Bayu Saputra; Nunik Hariyani; Veny Ari Sejati (Universitas Tribhuwana Tungga Dewi, 2026)
Instagram has become an important space for musicians to construct public identity through a complementary blend of visual and verbal messages. However, studies integrating the analysis of visual and verbal signs within the context of musicians' personal branding in Indonesia remain limited. This study aims to analyze the representation of Baskara Putra's self-image as a musician on the Instagram account @wordfang using Ferdinand de Saussure's semiotic approach. The research employs a qualitative method with an interpretive case study approach. The research data were sourced from seven purposively selected posts depicting the subject's musical activities. Data analysis focused on the relationship between signifier and signified formed through the integration of visual elements (photos) and verbal elements (captions). The findings reveal four main dimensions of self-image representation: professionalism and commitment to music-making, recognition of musical works, immersion in musical activity, and emotional connection with the audience. These four dimensions complement one another and construct a self-image that is not framed as instant success, but as an ongoing creative process. These findings affirm that the integration of visual and verbal signs on social media operates in a unified manner in shaping a musician's identity, while also enriching the application of Saussure's classical semiotics within the context of contemporary digital communication, and contributing empirically to studies of public figures' self-representation on social media platforms.Instagram telah menjadi ruang penting bagi musisi untuk mengonstruksi identitas publik melalui perpaduan pesan visual dan verbal yang saling melengkapi. Namun, kajian yang mengintegrasikan analisis tanda visual dan verbal dalam konteks personal branding musisi di Indonesia masih terbatas. Penelitian ini bertujuan menganalisis representasi citra diri Baskara Putra sebagai musisi pada akun Instagram @wordfang menggunakan pendekatan semiotika Ferdinand de Saussure. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus interpretatif. Data penelitian bersumber dari tujuh unggahan yang dipilih secara purposive dan memuat representasi aktivitas bermusik subjek. Analisis data difokuskan pada relasi antara penanda (signifier) dan petanda (signified) yang terbentuk dari integrasi elemen visual berupa foto dan elemen verbal berupa caption. Hasil penelitian mengungkap empat dimensi utama representasi citra diri, yaitu profesionalisme dan komitmen bermusik, pengakuan terhadap karya musik, penghayatan dalam aktivitas bermusik, serta hubungan emosional dengan audiens. Keempat dimensi tersebut saling melengkapi dan membentuk citra diri yang tidak dikonstruksi sebagai keberhasilan instan, melainkan sebagai proses berkarya yang berkelanjutan. Temuan ini menegaskan bahwa keterpaduan tanda visual dan verbal di media sosial beroperasi secara integratif dalam membentuk identitas musisi, sekaligus memperkaya penerapan semiotika klasik Saussure pada konteks komunikasi digital kontemporer serta memberikan kontribusi empiris bagi kajian representasi diri figur publik di platform media sosial.